A revisit to several issues in Zakat: a case study of Zakat collection centre – Majlis Agama Islam Wilayah Persekutuan (MAIWP) - Razali, Siti Salwani; Mohamed, Norhazwani (2010)
Zakat is one of the pillars of Islam and a major contributor to the development of Muslim economy. In Malaysia, zakat institution is under the State Islamic Religious Council which is governed by Islamic Religious Department in government department. Previously, state religious council are responsible to manage zakat collection and distribution office. However, starting 1991 there are number of zakat institution was corporatized in order to improve the performance of zakat collection and distribution. One of them is Zakat Collection Centre – Federal Territory Islamic Religious Council (MAIWP). This council was corporatized as the centre with subsidiary – Harta Suci Private Limited or it is called as Pusat Pungutan Zakat (PPZ).The main function of PPZ is to collect zakat throughout the federal territories of Kuala Lumpur, Putrajaya and Labuan, while the distribution of zakat to asnaf still maintained by Baitulmal Division. The centre of this research is focusing on the Zakat Collection Centre (PPZ) operation (mainly at Majlis Islam Wilayah Persekutuan). In this research, the main focus is to observe how this centre operates, and its performance after MAIWP has corporatized the organisation and also to study the issues arise in terms of collection and distribution of zakat. The process of observation is done by identifying the performance in 4 perspectives; consumer, financial, internal business process and learning and growth. Meanwhile, the external factor which will influence the performance of collection will be identified. The proposed method of analysis in this research is SLEPT analysis (for general environment), Balanced Scorecard analysis, SWOT analysis and TOWS Matrix analysis. By using this method of analysis, the performance and effectiveness of the organisation will be clearly discovered and some alternative solution will be recommended in the final stage of the research.